Los otros, sin patria: italianos en el litoral Caribe de Colombia a comienzos del siglo XX - Antonino Vidal Ortega; Giuseppe D’Amato Castillo (Caravelle)
This article explores the migration processes experienced by the northern coast of Colombia in the Caribbean Sea, focusing specifically on the arrival of Italians in the early decades of the twentieth century. Through the notarial records preserved in the Archivo Histórico del Atlántico, we survey their spreading process across the region as well as their economic activities that would enable them to evolve from laborers and specialized technicians in expanding agricultural borders, to prominent entrepreneurs in the most dynamic ports in Colombian Caribbean, developing their business from domestic to international markets.